Diagnosis and recommendation integrated system norms in custard apple (Indian Journal of Arid Horticulture, 2021)
A leaf sampling survey was caJTied out at 15 villages in states of Gujarat and Rajasthan during 2018-2020 and collected 338 samples in custard apple to develop diagnosis and recommendation integrated system (DRIS) norms. The leaf samples were collected in July month and the leaves present in the middle portion of the recently matured twig were analyzed for the nutrients , and classified based on standard deviation (SD) as deficient (< mean-8 /3 SD), low (mean-8/3 SD to mean-4 /3 SD), optimum (mean-4/3 SD to mean +4/3 SD), high ( mean +4/3 SD to mean +8/3 SD)) and very high ( > mean + 8/3 SD). The optimum concentration of nitrogen in the index leaf ranged from 1.96% to 3.06%, whereas phosphorus, potassium, calcium, magnesium, sulphur, iron, manganese, zinc and copper ranged from 0.13 to 0.17%, 0.59 to 0.99 %, 1.48 to 2.26%, 0.69 to 1.64%, 0.29 to0.45%, 126 to 328 ppm, 243 to 323 ppm, 38 to 56 ppm, and 21 to 36 ppm, respectively. This information may be used for developing DRIS and CND norms and to predict nutrient needs based on DRIS indices in nutrient management of custard apple trees.
Keywords: Custard apple; DRIS norms; CND; leaf sampling survey; nutrient management